Image_21.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
As evening sets in, Kusum activates a portable generator that runs on solar energy. Most roadside eateries do not have an electricity connection and rely on alternative methods to light their stalls post-sunset.